2007
DOI: 10.1680/bren.2007.160.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of a 30-year-old composite Preflex railway bridge

Abstract: Within the framework of the French National Research Project MIKTI dealing with 'composite steel-concrete footbridges and bridges for tomorrow', a loading test was performed in Belgium on a railway bridge deck consisting of simply supported composite 'Preflex' beams. The bridge was 30 years old at the time of the test so the timedependent stress redistribution between the steel of the girders and the concrete was almost stabilised. The bridge deck was loaded progressively by two heavy diesel-electric locomotiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Nowak and Tharmabala (1988) use bridge test data in conjunction with load-rating models to estimate what they refer to as safetyreserve. Similar studies were reported by Jáuregui and Barr (2004) and Staquet et al (2007).…”
Section: Output Response Validationsupporting
confidence: 91%
See 1 more Smart Citation
“…Nowak and Tharmabala (1988) use bridge test data in conjunction with load-rating models to estimate what they refer to as safetyreserve. Similar studies were reported by Jáuregui and Barr (2004) and Staquet et al (2007).…”
Section: Output Response Validationsupporting
confidence: 91%
“…This category is a completely model-free approach to SHM investigation. Examples of SHM deployments with anomaly detection components have been reported in Chang and Im (2000); ; Staquet et al (2007); Koo et al (2013); Roberts et al (2006Roberts et al ( , 2012; and Minardo et al (2012). Chandola et al (2009) give a detailed treatise on the fundamentals of detecting anomalies in data sets.…”
Section: Category 1: Anomaly Detectionmentioning
confidence: 99%
“…For small spans (below 25 m), the choice was precast girders or pre-bent composite girders of the Preflex type patented by the Belgian engineer A. Lipski in 1950 (e.g. Staquet et al, 2007). For medium-sized spans (25-60 m), prestressed concrete bridges would be cast in place with hollow box beams supporting tracks instead of composite steel-concrete structures.…”
Section: Prestressed Railway Bridgesmentioning
confidence: 99%